Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
<=> 162 + x = 67035 : 327
<=> 162 +x = 205
=> x = 205 - 162
=> x = 43
Vậy x = 43
327x ( 162 + x) =67035
162 + x = 67035 : 327
162 + x = 205
x = 205 - 162
x = 43
246:x+34:x=5
(246+34):x=5
280:x=5
x=280:5
x=56
360:x-126:x=6
(360-126):x=6
234:x=6
x=234:6
x=39
48 x X - X + 53 x X = 7900
48 x X - X x 1 + 53 x X = 7900
X x ( 48 - 1 + 53 ) = 7900
X x 100 = 7900
X = 7900 : 100
X = 79.
Vậy X = 79.
Hok tốt !
53 x 4 x 3 x 25 = 53 x ( 4 x 25 ) x 3
= 53 x 100 x 3
= 15900
327 x 73 + 27 x 327 = 327 x ( 73 + 27 )
= 327 x 100
= 32700
Hok Tốt nhen
a) \(52\times4\times3\times25\)
\(=\left(52\times3\right)\times\left(4\times25\right)\)
\(=156\times100\)
\(=15600\)
b) \(327\times73+27\times327\)
\(=327\left(73+27\right)\)
\(=327\times100\)
\(=32700\)
a,486:x-126:x=6
=>(486-126):x=6
=>360:x=6
=>x=360:6
=>x=60
b,725:x+175:x=5
=>(725+175):x=5
=>900:x=5
=>x=900:5
=>x=180
486:x-126:x=6
(486-126):x=6
360:x=6
x=360:6
x=60
725:x+175:x=5
(725+175):x=5
900:x=5
x=900:5
x=180
X + 126 = 480
\(\Rightarrow\)X = 480 - 126 = 354
X - 209 = 435
\(\Rightarrow\)X = 435 + 209 = 644
a) 246 : x + 34 : x = 5
( 246 + 34 ) : x = 5
280 : x = 5
x = 280 : 5
x = 56
b) 360 : x - 126 : x = 6
( 360 - 126 ) : x = 6
. 234 : x = 6
x = 234 : 6
x = 39
a, 246 : x + 34 : x = 5
( 246 + 34 ) : x = 5
280 : x = 5
x = 280 : 5
x = 56
Vay x=56
b , 360 : x - 126 : x = 6
( 360 - 126 ) : x = 6
234 : x= 6
x= 234 : 6
x= 39
Vay x=39
327 x ( 126 + x ) = 67 035
126 + x = 67 035 : 327
126 + x = 205
x = 205 - 126
x = 79
327 x ( 126 + x ) = 67035
126 + x = 67035 : 327
126 + x = 205
x = 205 - 126
x = 79
Vậy x = 79
_HT_